Prekių ir paslaugų pasiūlos kaita Lietuvos periodinės spaudos reklamoje 1918-1940 metais - Polkaitė, Giedrė (Lietuvos istorijos studijos, 2009)
Advertising in interwar Lithuania functioned as a source of information about new goods and services and also strove to create new demand and to promote new lifestyles, fashions, and habits. The aim of this article is to investigate the availability of goods and services in Lithuanian advertising during 1918-1940, to create periods in the tendencies in the change in their availability, and to analyse the dominant groups of goods and services. After calculating the general average of the goods and services advertised in the dailies *Lietuva*, *Lietuvos Aidas*, and *Lietuvos Žinios* during 1918-1940, it was discovered that the medical services and medicines group (18% of all the advertisements in *Lietuvos Aidas* and *Lietuva*; 11% of those in *Lietuvos Žinios*), cosmetics and household chemicals (13% and 18% respectively), and publications, bookshops, and print shops (8% and 10% respectively) were advertised the most intensively. Agricultural supplies (18%), cosmetics and household chemicals (17%), publications, bookshops, and print shops (7%), and banks (7%) were advertised the most in the publications *Lietuvos Ūkininkas* and *Ūkininko Patarėjas*. Alcoholic beverages were the least advertised in the studied publications. The greatest changes in the number of advertisements were observed in agricultural and industrial advertising as well as in the advertising for cosmetics and household chemicals. The intensity of the advertising for agricultural and industrial supplies fell from 13-14% during 1918-1922 to 0.3% in 1937 in the dailies *Lietuva* and *Lietuvos Aidas*. This type of advertising moved to specialised publications, in which no downtrend was observed: advertising for agricultural supplies comprised 16% of the entire number of advertisements for goods and services in *Lietuvos Ūkininkas* in 1919 and 13% in *Ūkininko Patarėjas* in 1938. Meanwhile, cosmetics advertising did not comprise even 0.5% of all the advertising during 1918-1919, but in the 1930s they became the most heavily advertised group of goods. This was caused by the establishment of local manufacturers in the market and the competition of their production. Not only did the intensity of cosmetics advertising increase but so did the supply of products and the circle of consumers. (Cosmetics were targeted not only at women but also at men and children, and an effort was made to attract rural buyers.) The advertisement of services, e.g., of physicians, various training courses, banks, tailors, cleaners, and hairdressers, occupied a solid (about 25-30%) percentage of the supply of advertising, especially during the first years of independence while manufacturing production was suspended due to the First World War and the young state’s political and economic instability. Of the aforementioned areas, physicians advertised the most. (In 1928, the advertisement of medical services comprised as much as 32% of the advertising in *Lietuvos Aidas*.) An analysis of the advertising during 1918-1940 allows one to state that vehicles from the most well-known manufacturers, as well as contemporary technical innovations, reached Lithuania. Sewing machines, electric light bulbs, bicycles, typewriters, and radios were especially heavily advertised in this group. The advertisement of refrigerators, cameras, vacuum cleaners, and electric shavers intensified in the 1930s. The advertisement of automobiles and electric goods was in general not especially intensive (comprising on average 4-5% of the entire number of advertisements). The number of advertisements for ready-to-wear clothing and footwear increased in the dailies that were studied. Fabric was advertised more in publications intended for the countryside. These facts allow one to make the assumption that the demand for ready-to-wear clothing increased in the cities. The concept of fashion, which dictated the manner of dressing, was already established in interwar Lithuanian advertising. The idea was promoted that new articles had to be bought each season. Food advertising was not abundant and on average comprised 4% of all the advertising. During the period under study, no changes in either the intensity or supply of such advertising were observed. New products (e.g., bouillon cubes, grain flakes, yoghurt, saccharin, decaffeinated coffee, and preserved foods) and delicatessens were the most intensively advertised. Advertisements for leisure pursuits (e.g., theatres, restaurants, holidays in local and foreign resorts, and dance lessons) were mostly placed in dailies and were almost completely absent in publications for rural residents.